Online Learning Analysis in the Currency of Civil Services in Building 21st Century Skills in SMA Negeri 2 Lintau Buo - Nelfisa Fitri; Maria Montessori (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research focuses on the study of online learning specifically for Civics Education subjects and its relation to the skills that students must possess in the 21st century. The researcher took a case study at SMA Negeri 2 Lintau Buo, with a qualitative approach through a series of observations and interviews. The results of this research include: :ImplementationPPKN online learning in building 21st century skills is that PPKN teachers at SMA 2 Lintau use the WA (Whatsapp) application because students and teachers are already familiar with the application in sharing photos, videos, files and others. In building 21st century skills in online PPKN learning, some PPKN teachers give individual assignments to students by asking them to write down their opinions on current cases related to the material provided, such as executive, legislative and judicial institutions (class X), human rights (class X). XI), and Rights and Obligations (Class XII). The constraints faced by PPKN teachers in delivering online learning are due to the limited time for PBM during the pandemic; students lack motivation in learning and have not been able to explore the potential that exists in themselves; many students are not present during online lessons so that communication does not go well because the signal is not good, there is no data package and others; students have not been able to train themselves to think critically and creatively because most of the learning and other subject assignments given do not build 21st century skills.